Assessing Names? Effects of Name-Based Stereotypes on Teachers' Evaluations of Pupils' Texts. (2nd January 2017) - Aldrin, Emilia
Abstract : This study investigates the effects of name-based ethnic and social stereotypes on teachers' grading of pupils' texts in contemporary Sweden. A total of 113 practicing Swedish high school teachers assessed an authentic pupil text with one of three male names inserted, each intended to evoke a certain ethnic or social stereotype. Participants also explained their grading and answered questions regarding key features of the text. Both quantitative and qualitative analyses were conducted. The study concludes that name-based stereotypes generally have little influence on teachers' assessment in contemporary Sweden. Results indicate a systematic but small and not statistically relevant name effect. A negative effect can be seen with regard to an ethnically marked name. This effect is shown when teachers evaluate language proficiency, but not for other features of the text. Regarding socioeconomically marked names there is little systematic effect. The study also suggests, however, that there may be compensatory mechanisms limiting the name effect.